1989
DOI: 10.1002/jlac.198919890289
|View full text |Cite
|
Sign up to set email alerts
|

On the Chemistry of Latrunculins A and B

Abstract: The chemical behavior of latrunculins A (1) and B (2) (Lat A and B) under a variety of reaction conditions is described. The combination of the macrolide, the THP‐lactol, and the 2‐thiazolidinone rings was found to result in interesting unpredicted chemical transformations. The structures of two new Lats, 6,7‐epoxy‐Lat A (3) and Lat M (4) isolated from Latrunculia magnifica are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 13 publications
2
48
0
Order By: Relevance
“…[5, 42,59] In line with the results discussed above, it is reasonable to assume that this cleavage is en- thalpically driven by relief of the 1,3-transannular interaction between the anomeric -OH group and the lactone moiety on the tetrahydropyran ring.…”
Section: A Novel Degradation Pathwaymentioning
confidence: 73%
See 1 more Smart Citation
“…[5, 42,59] In line with the results discussed above, it is reasonable to assume that this cleavage is en- thalpically driven by relief of the 1,3-transannular interaction between the anomeric -OH group and the lactone moiety on the tetrahydropyran ring.…”
Section: A Novel Degradation Pathwaymentioning
confidence: 73%
“…[42] It is assumed that hemiacetal 30 with an axially oriented -OH group at C13 (Lat-B numbering) is predisposed to eliminate H 2 O to relieve the strain resulting from the unfavorable 1,3-transannular interaction with the anomeric hydroxyl group. The loss of a second molecule of H 2 O will then rapidly ensue under the acidic conditions due to the stabilized character of the incipient oxocarbenium cation 32.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas essentially all post facto chemical derivatizations of latrunculin A or B reported in the literature led to a complete loss of the actin-binding capacity of these marine natural products (24)(25)(26), a series of fully functional synthetic analogues is now presented, some members of which even surpass the natural lead compounds in terms of bioactivity. Because none of the synthetic analogues is available from the natural products without unreasonable effort, this study highlights the enabling power of the concept of ''total synthesis-driven'' searches for SAR profiles of complex bioactive molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these truly remarkable physiological properties of the latrunculins and their widespread use as biochemical tools, the present understanding of the structure͞activity relationship (SAR) of these exquisite actin binders is fairly limited (24)(25)(26). While derivatizations of the natural products showed that a free hemiacetal moiety at C.17 (Lat-A numbering) and an unprotected N-atom of the thiazolidinone ring are pivotal for eliciting a biological response, ʈ a more detailed mapping of the SAR is warranted.…”
mentioning
confidence: 99%
“…[4,5] Despite the truly remarkable properties of the latrunculins and their widespread use as biochemical tools, the understanding of the structure-activity relationships (SAR) of these exquisite actin binders is fairly limited. [6] As a first step towards a synthesis-driven mapping of the structural elements essential for biological activity, a concise total synthesis of latrunculin B (1) was devised which is flexible enough to allow structural variations at a later stage. This flexibility was ensured by disconnecting 1 into three simple building blocks (Scheme 1) that are easy to modify and can be efficiently assembled through aldol chemistry, esterification, and formation of the macrocycle by the novel ring-closing alkyne metathesis (RCAM)/Lindlar reduction manifold.…”
mentioning
confidence: 99%